Geneza horroru jako gatunku - Trofymenko, Anastasija (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
This article examines the origin of horror as a genre within the cluster of all horror literature genres. The structure of genological-typological evolution of these genres has been analysed. It has been proven that horror, due to its specificity, should be referred to this group of genres which are realized in literature on the basis of genre memory.
The Origin of Horror as a Genre
Keywords: genre; origin; horror; genre memory; genological-typological evolution; gatunek; geneza; pamięć gatunku; ewolucja genologiczno-typologiczna